Traditional Chinese medicine for psoriasis vulgaris: A Protocol of a prospective, multicenter cohort study. Issue 41 (9th October 2020) - Guo, Xinwei; Zhou, Dongmei; Sun, Liyun; Wang, Ping; Qu, Jianhua; Zhang, Cang; Wang, Yan; Chen, Zhaoxia; Li, Bo; Hu, Jing; Lin, Zhimiao; Shi, Fei; et al.
Abstract: Introduction: The incidence of psoriasis vulgaris is increasing worldwide. Chronic recurrence of the disease, as well as accompanying cardiovascular disease, metabolic syndrome, and depression has affected the physical and mental health of these patients. Psoriasis vulgaris is a difficult and major disease in the dermatology field. Short-term curative effects using conventional therapy for psoriasis vulgaris has made major strides. However, traditional Chinese medicine (TCM) treatment has long-term curative advantages for psoriasis vulgaris but lacks the scientific and clinical evidence for its use. This study intends to demonstrate and provide scientific and clinical evidence for the use of TCM to delay the recurrence of psoriasis vulgaris. Methods and analysis: This will be a prospective, multicenter cohort study. We intend to recruit 1521 psoriasis vulgaris patients from 14 hospitals in Beijing, Tianjin, and Hebei. Treatment will be based on the diagnosis specifications and clinical practice guidelines of TCM and conventional therapy. During inclusion and the subsequent follow-up period, doctors through electronic case reports will collect different therapeutic TCM regimens and conventional therapy that were administered. Information on life condition, skin lesions at each visit, World Health Organization Quality of Life Instruments, Zung Self-rating Anxiety Scale, Zung Self-assessment of Depression, laboratory examinations, incidence of new rash and recurrence during the remission and recurrence stages will be recorded. Ethics and dissemination: The clinical trial protocol for this study was approved by the ethics committee of the Beijing hospital of TCM affiliated to capital medical university (Ethics number: 2019BL02-010-02). We will publish and present our results at national and international conferences and in peer-reviewed journals specialized in dermatology. Trial registration: This protocol has been registered in clinicaltrials. gov (ChiCTR1900021629)